2021
DOI: 10.1002/adfm.202007555
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Controlled Growth Factors Release on Tetrapodal ZnO‐Incorporated 3D‐Printed Hydrogels for Developing Smart Wound Scaffold

Abstract: Advanced wound scaffolds that integrate active substances to treat chronic wounds have gained significant recent attention. While wound scaffolds and advanced functionalities have previously been incorporated into one medical device, the wirelessly triggered release of active substances has remained the focus of many research endeavors. To combine multiple functions including light-triggered activation, antiseptic, angiogenic, and moisturizing properties, a 3D printed hydrogel patch encapsulating vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 77 publications
1
88
0
Order By: Relevance
“…Therefore, loading growth factors or peptides that promote angiogenesis in hydrogels has become a feasible strategy. For example, Siebert et al (2021) developed a 3D printing hydrogel patch coated with VEGF and modified by tetrapod zinc oxide (t-ZnO) particles with photoactivity and antibacterial effect. The controlled release of VEGF could be achieved by chemical modification of t-ZnO and activation with ultraviolet/visible light.…”
Section: Functionalization Of Hydrogels For Wound Healingmentioning
confidence: 99%
“…Therefore, loading growth factors or peptides that promote angiogenesis in hydrogels has become a feasible strategy. For example, Siebert et al (2021) developed a 3D printing hydrogel patch coated with VEGF and modified by tetrapod zinc oxide (t-ZnO) particles with photoactivity and antibacterial effect. The controlled release of VEGF could be achieved by chemical modification of t-ZnO and activation with ultraviolet/visible light.…”
Section: Functionalization Of Hydrogels For Wound Healingmentioning
confidence: 99%
“…Recently, various functional hydrogels have been widely used to promote wound healing. [108][109][110][111][112][113][114][115][116][117][118] Chang and coworkers developed a unique bioglass (BG)/oxidized sodium alginate (OSA) composite hydrogel that showed excellent bioactivity to promote vascularization and accelerate tissue regeneration. 119 On the one hand, the BG improves the tissue bonding strength by providing an alkaline microenvironment to stimulate bond formation between the OSA and the amino groups on the surrounding tissue.…”
Section: Wound Healingmentioning
confidence: 99%
“…Stimuli-responsive delivery systems are smart approaches for the controlled and sitespecific release of molecules [168]. Siebert et al (2021) proposed a multifunctional wound hydrogel patch containing VEGF decorated with photoactive tetrapodal zinc oxide and activated through ultraviolet/visible light stimulus. The stimulus-responsive system provided controlled release of VEGF with green light exposure over 120 s. Two concentrations of VEGF were studied and the release rate was not affected by VEGF concentration.…”
Section: Peptides and Proteinsmentioning
confidence: 99%
“…Additionally, tetrapodal zinc oxide features antimicrobial activity, which is important to the adequate wound healing process, in agreement with the in vitro antibacterial assays. The in vivo studies of the wound healing model showed that the 3D-printed scaffold with tetrapodal zinc oxide and VEGF promoted faster wound healing, by enhanced anti-inflammatory, angiogenesis and cell proliferation effects [151].…”
Section: Peptides and Proteinsmentioning
confidence: 99%